[Spichlerze przy ul. Chmielnej] [aut. odb. Karol Nowaliński]. - Nowaliński, Karol (1935- ). (Karol Nowaliński, 1986)
Przedstawia spichlerze przy ul. Chmielnej od nr 66 do Mostu Krowiego. Ujęcie z nabrzeża, ok. 1920 r.